IMPLEMENTASI LESSON STUDY LEARNING COMMUNITY UNTUK MENINGKATKAN PENALARAN ALJABAR MAHASISWA PADA MATERI FUNGSI PEMBANGKIT - Nur Fitriyah Indraswari Indraswari; Agus Wahdian (Jurnal Muara Pendidikan, 2024)
This research aims to determine the improvement in each algebraic reasoning indicator in solving generating function problems after implementing the M-APOS approach based on the lesson study learning community. This type of research is classroom action research with a qualitative approach. The lesson study stages are similar to classroom action research (PTK). The research subjects were 23 odd-semester STKIP PGRI Sumenep mathematics education study program students who had passed the prerequisite courses. The research instrument is a problem-solving task related to the generating function and a lesson study observation sheet. Data were analysed using qualitative descriptive analysis by describing the percentage of data obtained by indicators of algebraic reasoning based on the results of observations of the implementation of lesson study and problem-solving tasks. The increase in algebraic reasoning in the indicators of pattern finding, pattern discovery, and generalization, respectively, amounted to 56.17%, 52.73%, and 49.32%.